Analisis faktor yang mempengaruhi penerimaan pendapatan asli daerah Kabupaten Muaro Jambi - Abunyani Abunyani; Parmadi Permadi; Erfit Erfit (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2019)
This study, entitled factor analysis affecting the revenue of original region of Muaro Jambi Regency. The purpose of this study is to analyze the effect of gross domestic product per province and the number of residents on the local revenue in Muaro Jambi District during 2005-2015. The methods of analysis are used in this study qualitative descriptive analysis and quantitative analysis by using an analysis tool, like a multiple regression analysis models. The results of this study based on the calculation of statistical test show hypothesis test using t statistic show partially significant variable is GDP per province has a positive effect on revenue of locally-generated revenue (PAD) in Muaro Jambi regency, while population growth has no positive effect on the locally-generated revenue (PAD) in Muaro Jambi regency. Based on the statistical f test shows all the coefficients of multiple linear regression or variable (Overall) of regression coefficients consisting of GDP per province and Population positively affect the revenue of locally-generated revenue (PAD) in Muaro Jambi regency. Keywords: Locally-generated revenue, Gross regional domestic product, Total population